Hubungan Pengetahuan Gizi Ibu, Pendapatan, Ketahanan Pangan Keluarga dengan Status Gizi Siswa MTs Muhammadiyah Pemalang - Oktaviasih, Astri Ayu; Sartono, Agus; Susantini, Purwanti; Ayuningtyas, Rr. Annisa (Universitas Muhammadiyah Semarang, 2023)
Adolescence is a unique period in terms of behavior to meet nutritional needs. The nutritional status of the adolescent is interfered with by sociodemographic variables. This study aims to analyze the relationship between mother’s nutritional knowledge, income, and household food security with the nutritional status of students at MTs Muhammadiyah 02 Pemalang. A cross-sectional study was conducted on 76 students selected by systematic random sampling. The respondents of this study are the mother and the family. Data on mothers’ nutrition knowledge, family income, and food security were collected using questionnaires. The relationship of the variables was analyzed by Pearson correlation. The study found that 22.4% of students are underweight, and 11.8% of students are overweight. 52.6% of respondents haveadequate nutrition knowledge, 40.8% of respondents' families have low income, and 57.9% are food insecure. There is no relationship between mothers’ nutritional knowledge and family food security (p =0.099), there is a relationship between mothers’ nutritional knowledge and student nutritional status (p =0.014), there is a relationship between family income and student nutritional status (p = 0.000), there is no relationship between food security families with the nutritional status of students (p = 0,888). Mothers’ nutritional knowledge and family income are related to the nutritional status of the student.Keyword : Food security, income, mother’s nutritional knowledge, nutritional status